2012
DOI: 10.1016/j.ceca.2012.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent physiologic and pathologic stimulus-metabolic response coupling in hepatocytes

Abstract: A recurrent paradigm in calcium signaling is the coordination of the target response of the calcium signal with activation of metabolic energy production to support that response. This occurs in many tissues, including cardiac and skeletal muscle where contractile activity and ATP production are coordinately regulated by the frequency and amplitude of calcium transients, endocrine and exocrine cells that use calcium to drive the secretory process, and hepatocytes where the downstream targets of calcium include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 84 publications
2
23
1
Order By: Relevance
“…Although NADH oscillations were observed in ex vivo model systems, such as pancreatic islets (Luciani et al, 2006), isolated cardiomyocytes (Zhou et al, 2011), perfused liver (Gaspers et al, 2012) and isolated acini from exocrine glands (Bruce et al, 2004; Voronina et al, 2002), their average period was much slower than what we observed in vivo (12.1 ± 3.1 sec, Av. ± S.D., N=19 vs. tens of seconds to minutes).…”
Section: Resultscontrasting
confidence: 64%
“…Although NADH oscillations were observed in ex vivo model systems, such as pancreatic islets (Luciani et al, 2006), isolated cardiomyocytes (Zhou et al, 2011), perfused liver (Gaspers et al, 2012) and isolated acini from exocrine glands (Bruce et al, 2004; Voronina et al, 2002), their average period was much slower than what we observed in vivo (12.1 ± 3.1 sec, Av. ± S.D., N=19 vs. tens of seconds to minutes).…”
Section: Resultscontrasting
confidence: 64%
“…Moreover, mitochondrially targeted ROS biosensors have revealed increases in mitochondrial superoxide and hydrogen peroxide levels in primary hepatocytes only after sustained hormone‐induced elevations in [Ca 2+ ] i (Gaspers et al . ). We have also reported that mitochondrial Ca 2+ levels and mitochondrial ROS formation are elevated in hepatocytes from alcohol‐fed rats compared to control (Wang et al .…”
Section: Discussionmentioning
confidence: 97%
“…We have previously reported that susceptibility to mitochondrial PTP transition in isolated liver mitochondria and hepatocytes is enhanced by alcohol feeding (Pastorino & Hoek, ) and sustained increases in cytosolic Ca 2+ can stimulate mitochondrial ROS production (Gaspers et al . ). Therefore, we hypothesized that pathological conditions that alter hormone‐dependent Ca 2+ signalling in the liver may have a profound impact on the health of individual hepatocytes and the organ as a whole.…”
Section: Introductionmentioning
confidence: 97%
“…The upregulation of Krebs cycle and other Ca 2+ -dependent mitochondrial reactions underpins the regulation of mitochondrial ATP production required for efficient stimulus-metabolism coupling (e.g. [77, 157, 166], reviewed in [55, 156]).…”
Section: Er-mitochondria Junctions As Signalling Nanodomainsmentioning
confidence: 99%